PENERAPAN PRINSIP GOOD GOVERNANCE TERHADAP EFEKTIVITAS PERENCANAAN PEMBANGUNAN BADAN PERENCANAAN PEMBANGUNAN DAERAH KOTA KENDARI - Haeruddin, Karnila; Tawai, Adrian; Yusuf, Muhammad (REZ PUBLICA, 2019)
The purpose of this study was to determine the application of the principles of good governance to the effectiveness of regional development planning in Kendari City. The population in this study were all employees of the Kendari City Regional Development Planning Agency (Bappeda), amounting to 143 people. In addition, in determining the sample, it took 25% of the total population of 143 people to produce a value of 35.75 and was filled into 36 people. So the sample in this study amounted to 36 people. In addition to the data obtained from the samples obtained, in completing the data the researcher also obtained information from outside communities or government elements who knew the problem being discussed. The results showed that the application of the principles of good governance in Bappeda Kendari City in terms of the 3 main principles of Good Governance namely accountability, transparency and participation were quite good. This means that the Kendari City Bappeda has implemented good governance. On the other hand, the effectiveness of development planning in Bappeda Kendari City has fulfilled three dimensions. Namely implementation, applicable, in strategic planning. In this case, the three dimensions show good and adequate categories.